UPAYA PENINGKATAN HASIL BELAJARMELALUIMETODE PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT)MATA PELAJARAN PKN PADA SISWAKELAS V SD NEGERI 165730 TEBING TINGGI - Pujawati Pujawati (Universitas Negeri Medan, 2019)
The aim of this research is to improve learning outcomes on civic education subject through Value Clarification Technique (VCT) method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class V, SDN 165730 Tebing Tinggi which amounted to 33 students. This study used a qualitative descriptive analysis technique. Based on data obtained from the measurement of the student learning outcomes on the cycle I of 81,81 % and cycle II amounted to 96,96 % note there is an increase in student learning outcomes. This means learning the civic education using Value Clarification Technique (VCT)can improve learning outcomes in class V SDN 165730 Tebing Tinggi. Key word: VCT, Civics, PKn